Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1038/oby.2012.67
|View full text |Cite
|
Sign up to set email alerts
|

The Glucagon Receptor Is Involved in Mediating the Body Weight‐Lowering Effects of Oxyntomodulin

Abstract: Oxyntomodulin (OXM) is a peptide secreted postprandially from the L-cells of the gut that has a weak affinity for both the glucagon-like peptide-1 receptor (GLP1R) and the glucagon receptor (GCGR). Peripheral administration of OXM in humans and rodents causes weight loss reducing food intake and increasing energy expenditure. It has been suggested that OXM modulates energy intake solely through GLP1R agonism. Because glucagon decreases food intake in rodents and humans, we examined whether activation of the GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 28 publications
(58 reference statements)
3
74
1
Order By: Relevance
“…Beneficial effects of both treatment regimens were independent of alterations in body weight or energy intake. Previous studies have indicated that glucagon can decrease food intake (Habegger et al 2010, Kosinski et al 2012; however, our studies with peptide-based glucagon antagonists suggest that contrasting elevations of energy intake do not occur with glucagon receptor inhibition , McShane et al 2014. This probably reflects the complex neural pathways and plasticity involved in the regulation of feeding and energy balance (Dockray & Burdyga 2011).…”
Section: Figurecontrasting
confidence: 45%
“…Beneficial effects of both treatment regimens were independent of alterations in body weight or energy intake. Previous studies have indicated that glucagon can decrease food intake (Habegger et al 2010, Kosinski et al 2012; however, our studies with peptide-based glucagon antagonists suggest that contrasting elevations of energy intake do not occur with glucagon receptor inhibition , McShane et al 2014. This probably reflects the complex neural pathways and plasticity involved in the regulation of feeding and energy balance (Dockray & Burdyga 2011).…”
Section: Figurecontrasting
confidence: 45%
“…Recent observations suggest that the activation of glucagon receptor stimulates fibroblast growth factor 21 (FGF21) production and secretion by the liver and that FGF21 mediates, at least partly, the effects of glucagon on energy expenditure and lipid metabolism (Habegger et al 2013). The beneficial effects of the combined activation of GLP-1 and glucagon receptors are also supported by reports showing that oxyntomodulin which is produced by L-cells and is a weak coagonist of glucagon and GLP-1 receptors suppresses appetite, increases energy expenditure, and reduces weight loss (Cohen et al 2003;Wynne et al 2006;Du et al 2012;Kosinski et al 2012). These combinatorial therapies, although very promising, still require careful examination for their applications to the long-term treatment of diabetes, obesity, or the metabolic syndrome.…”
Section: Combinatorial Therapies For the Treatment Of Obesity And Diamentioning
confidence: 93%
“…However, side-by-side comparison of OXM to a molecule in which 728 the GcgR activity of OXM had been completely removed showed a superior ability of OXM to lower body weight and fat mass. This suggests that the glucagon receptor activity of OXM is a participant in pharmacologically induced weight loss (Kosinski et al, 2012).…”
Section: A Glucagon-like Peptide 1/glucagon Coagonismmentioning
confidence: 99%